Why Should Non-Human Victims Be Recognized? Reflections on the Protection of Non-Human Victims in Environmental Crimes in Indonesia - Muhamad Agil Aufa Afinnas (Universitas Sultan Ageng Tirtayasa, 2026)
Environmental crimes not only result in human victims but also non-human victims. However, the reality of law enforcement against environmental crimes in Indonesia shows that protection for non-human victims remains inadequate. This research is based on such concerns. This research aims to analyze the theoretical and practical perspectives on the recognition of the intrinsic value of non-human entities and the justification for recognizing and protecting non-human victims in environmental crimes in Indonesia. This research is doctrinal legal research. The results of the study indicate that, first, recognition of the intrinsic value of non-human entities can be found in both theoretical and practical perspectives. Second, the condition of protection for non-human victims in environmental crimes in Indonesia indicates the current need to provide better recognition and protection for non-human victims. The root of this problem is the lack of normative recognition of non-human victims. There are at least four justifications why non-human victims in environmental crimes must be protected: ethical considerations, considerations of creating justice, considerations from the perspective of ecological function, and considerations of the legal function to protect the balance of the ecological system. These findings also emphasize the urgency of strengthening the recognition and protection of non-human victims in environmental crimes in Indonesia.